Implementasi Deep Learning dalam Meningkatkan Pemahaman dan Pengamalan Nilai-Nilai Keislaman Siswa - Luqiya Luthfiana; Muhammad Sugianto; Mohamad Solihin (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to comprehensively describe the implementation of deep learning in improving students' understanding and practice of Islamic values ​​at SMP Unggulan Zainul Hasan Genggong Probolinggo. This study uses a qualitative approach with a case study research type to explore the phenomenon in depth in a natural context. Data collection techniques were carried out through observations of the learning process, in-depth interviews with teachers and students, and documentation of learning and religious activities. Data analysis was carried out through the stages of data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that the implementation of deep learning through the principles of mindful learning, meaningful learning, and joyful learning can improve students' understanding of Islamic values ​​in a more reflective, contextual, and meaningful manner. In addition, this learning also has a significant impact on improving the practice of values, such as honesty, responsibility, discipline, social concern, and consistency in carrying out worship. Thus, this approach is effective in shaping students' religious character in a holistic, adaptive, and relevant way to the daily lives of today's students